Intellectual property right among small medium enterprise (SMEs): A case of food & beverage company in Kedah Malaysia - Ahmad, Azliza; Anuar, Herman Shah (2015)
IPR has become the common phrase among industry practitioner when they want to deal business in the international market. SME has to face the challenge of equipping themselves with all the necessary measures in making sure businesses survived and sustained. The issue is more towards competitive and productivity among them. The crux of the matter, this study will investigate the practices implemented among SMEs in the same category which is food and beverage company. The method used to obtain data is through a survey which includes an interview. This involved respective personnel in the company.Previous study will be reviewed to gain better understanding of how the IPR would really enhance the F&B company's productivity in the long run.The ramifications of the findings, would reveal how the practices of IPR among SMEs would yield significant improvement in company revenue. This can serve as a guideline for better understanding of how IPR practices between SMEs being implemented.The study found that use of brand innovation and IPR can increase competition and productivity.However, the SMEs is not using IPR lack of knowledge.Thus, future studies will need to examine in detail what factors, SMEs do not apply to drivers of IPR.